Conserving land, protecting water - Bossio, D.; Bossio, D.; Geheb, K.; Geheb, K. (Wallingford :CABI, 2008)
This volume follows from a project of the Comprehensive Assessment of Water Management in Agriculture that brought together experts in fields ranging across the social sciences, ecology, agricultural sciences, soil and water science, political science and development studies to examine examples of success in reversing land degradation, understand their importance, and explore the essential relationships and linkages between land use and water management within them. This book aims to improve our understanding of these linkages, and examines the relationships between land, water and social systems, emphasizing that it is only such an integrated view that will yield a better understanding of how positive outcomes can be generated. There are 14 chapters divided into three sections. The first section briefly reviews the literature on the status of the world's ecosystems with respect to land and water resources and global patterns of land and water degradation, and then focuses on newer insights into how we view the impact of degradation, the essential linkages between the management of land and water, and the social processes that determine land-use decision making and their interaction with land degradation. The second section of the book explores improved management options, both in theoretical contexts and through practical case studies focusing on the integration of land and water within social contexts and management frameworks at larger scales. Section three presents in detail a large compilation of successful case studies gathered under the 'bright spots' project.
Keywords: PP200 - Water Resources; PP300 - Land Resources; PP600 - Pollution and Degradation; UU485 - Social Psychology and Social Anthropology, (New March 2000)